17β-Estradiol inhibits estrogen binding protein-mediated hypha formation in Candida albicans. (August 2017) - Kurakado, Sanae; Kurogane, Rie; Sugita, Takashi
Abstract: Candida albicans is one of the most prevalent and clinically important fungal pathogens. The ability to change form depending on environmental stress is an important microbial virulence factor. A survey of compounds that inhibit this morphological change identified various steroids, including 17β-estradiol. Interestingly, C. albicans has proteins capable of binding to steroids, including estrogen binding protein (Ebp1). Estrogens regulate cell differentiation and proliferation in humans through estrogen receptor proteins. To determine whether EBP1 regulates a virulence factor, we investigated the effect of 17β-estradiol on the morphological transition of C. albicans using an ebp1 deletion mutant. Treatment with 10 μg/mL of 17β-estradiol inhibited hypha formation, whereas its effect on the ebp1 deletion mutant was decreased compared to that on the wild-type and revertant strains. These data suggest a new pathway for the yeast-to-hypha transition via EBP1 in C. albicans . Highlights: Candida albicans has an estrogen binding protein (Ebp1). 17β-Estradiol inhibits hypha formation in C. albicans. The effect on the ebp1 deletion mutant is decreased compared to that on the WT.